The Analysis Of Tense In Writing A Recount Paragraph Of University Students Of ITP Markandeya Bali - Ni Komang Sinta Dewi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
The study entitled "Tense Analysis of Tense in Writing Recount Paragraphs of University Students of ITP Markandeya Bali " aims to analyze the use of tense and the types of errors that commonly occur in writing recount paragraphs by ITP Markandeya Bali students in the second semester. Mastering tense is the most important thing for writing an English text. Especially in writing recount paragraphs that retell an event in the past. However, the results of previous research and theories found that many students still have difficulty in using the correct tense structure. In this study, the method used is a qualitative descriptive method involving 18 second semester students of the English Language Education Study Program at ITP Markandeya Bali. In this study, data collection techniques were through interviews, documentation, and document observation. Data were obtained from the results of student writing, namely writing recount paragraphs. The data was analyzed to find the types of tenses used by students, then the errors were classified based on (Dulay et.al., 1982) theory (misinformation, omission, addition and misodering). Based on the research results, the most frequently used tense by students when writing recount paragraphs was the simple past tense (used 136 times). Although students correctly selected the tense, errors were still found. Of the 179 tenses used, 60 errors were found. The types of errors found were misinformation (47.3%), misordering (25%), omission (16.7%), and final addition (11.1%). To overcome this problem, practice in grammar and correct writing is required. Keywords: Recount Paragraph; Tense; Simple Past Tense; Writing Skill.